2021
DOI: 10.1017/s0007123421000119
|View full text |Cite
|
Sign up to set email alerts
|

Are Policy Analogies Persuasive? The Household Budget Analogy and Public Support for Austerity

Abstract: Public opinion on complex policy questions is shaped by the ways in which elites simplify the issues. Given the prevalence of metaphor and analogy as tools for cognitive problem solving, the deployment of analogies is often proposed as a tool for this kind of influence. For instance, a prominent explanation for the acceptance of austerity is that voters understand government deficits through an analogy to household borrowing. Indeed, there are theoretical reasons to think the household finance analogy represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…The core conceptual focus of research in this field is whether (and to what degree) a given rhetorical element can persuade citizens to change their political views. For instance, though politicians may construct very different metaphors to argue about the economy (Barnes and Hicks 2019), crime (Thibodeau and Boroditsky 2011), and healthcare (Schlesinger and Lau 2000), it might be the use of metaphor itself that is “essential to their persuasiveness” (Charteris‐Black 2011, 2). Existing work has considered the effects of a wide range of rhetorical elements on public opinion, including populist rhetoric (Atkins and Finlayson 2013; Bos, Van der Brug, and de Vreese 2013; Hameleers, Bos, and de Vreese 2017; Hameleers and Schmuck 2017); negative or ad hominem attacks (Lau, Sigelman, and Rovner 2007); morality‐ and values‐based appeals (Jung 2020; Nelson 2004); appeals based on expected costs and benefits of policy (Jerit 2009; Riker 1990); and the use of expert cues and endorsements (Atkins and Finlayson 2013; Boudreau and MacKenzie 2014; Dewan, Humphreys, and Rubenson 2014).…”
Section: Rhetoric Persuasion and Public Opinionmentioning
confidence: 99%
“…The core conceptual focus of research in this field is whether (and to what degree) a given rhetorical element can persuade citizens to change their political views. For instance, though politicians may construct very different metaphors to argue about the economy (Barnes and Hicks 2019), crime (Thibodeau and Boroditsky 2011), and healthcare (Schlesinger and Lau 2000), it might be the use of metaphor itself that is “essential to their persuasiveness” (Charteris‐Black 2011, 2). Existing work has considered the effects of a wide range of rhetorical elements on public opinion, including populist rhetoric (Atkins and Finlayson 2013; Bos, Van der Brug, and de Vreese 2013; Hameleers, Bos, and de Vreese 2017; Hameleers and Schmuck 2017); negative or ad hominem attacks (Lau, Sigelman, and Rovner 2007); morality‐ and values‐based appeals (Jung 2020; Nelson 2004); appeals based on expected costs and benefits of policy (Jerit 2009; Riker 1990); and the use of expert cues and endorsements (Atkins and Finlayson 2013; Boudreau and MacKenzie 2014; Dewan, Humphreys, and Rubenson 2014).…”
Section: Rhetoric Persuasion and Public Opinionmentioning
confidence: 99%
“…
Household analogy' is a form of rhetoric that equates the government budget with a household one and is typically used to advocate fiscal consolidation through the emphasis on the threat of bankruptcy. The present paper sets its context in Japan and extends the survey experiment conducted by Barnes and Hicks (2021), which found the household analogy in the UK to be ineffective in persuading the public. Our results replicated their null findings in Japan.
…”
mentioning
confidence: 76%
“…If a median-income American family spent money like the U.S. government, it would have spent all of its earnings, and then put over $46,000 on the credit card in 2020 even though it was already $474,000 in debt. (The Heritage Foundation, 2022) To examine whether this household analogy successfully persuades the public, Barnes and Hicks (2021) ran a series of observational and experimental studies in the UK and concluded that the household analogy is not effective in changing public attitudes toward government fiscal management. This paper replicates and extends their experiment in the context of Japan.…”
Section: Introductionmentioning
confidence: 99%
“…For example, individuals or opposition parties could not clearly attribute the crisis to fiscal largesse, domestic or international banks, previous government policies, or—for European countries—the actions of the EU. This in turn meant that previous “narratives” normally used to justify various fiscal policies in response to other recessions would be more muted or less credible ( Barnes and Hicks, 2021b ; Bansak, et al 2021 ). Therefore, we would expect that the clear external exogenous origin of the crisis should increase fiscal intervention support.…”
Section: Background Motivation and Hypothesesmentioning
confidence: 99%